The Libyan Diplomatic Stance on the 1956 Tripartite Aggression against Egypt and Its Impact on Libyan–British Relations - Al-Zarqa Salem Mohammed Muftah (Journal of Libyan Academy Bani Walid, 2025)
This study seeks to stand on the position of the people of Libya and the government of the triple number on Egypt and to study the circumstances of this position in light of the presence of British military bases inside the Libyan lands, and the treaties that linked them to the countries that have aggression against Egypt. Regarding the deterioration of the situation inside the British bases and camps in Libya, we will also try to clarify the role of the Egyptian embassy in inciting public opinion in Libya, according to the available sources and newspapers that carried information about the views and trends of Libyan politics towards this issue.